Forceps versus snare polypectomies in colorectal cancer screening: are we adhering to the guidelines? - Britto-Arias, Martha; Waldmann, Elisabeth; Jeschek, Philip; Gessl, Irina; Sallinger, Daniela; Bannert, Christina; Weber, Michael; Trauner, Michael; Weiss, Werner; Ferlitsch, Arnulf; Ferlitsch, Monika (Endoscopy, 2015)
Background and study aims: European guidelines for quality assurance in colorectal cancer screening recommend snare resection for polyps > 5 mm. The aim of this study was to investigate polypectomy technique according to lesion size and shape, and to assess adherence of endoscopists enrolled in the national quality assurance program to the European guidelines.Patients and methods: This cohort study included screening colonoscopies performed between 2007 and 2013 within a quality assurance program in Austria. Resection technique was analyzed according to lesion characteristics and endoscopy facility (private practices, hospitals, outpatient clinics) before publication of the EU guidelines (2007 – 2010) and adherence to the guidelines after publication (2011 – 2013). All surveillance colonoscopies and examinations with missing data were excluded. Results: A total of 128 969 screening colonoscopies performed by 278 endoscopy units were included. The polyp detection rate was 39.6 % (n = 47 797) and 95.6 % of polyps were resected. Of polyps ≥ 5 mm, 46.0 % were resected using forceps and were therefore not treated in accordance with the guidelines. Forceps polypectomy of lesions 5 – 10 mm and > 10 mm decreased significantly in hospitals after implementation of the guidelines (both P < 0.0001). In private practices, there was no difference in forceps usage for polyps of 5 – 10 mm (P = 0.41) before and after the guidelines, and for polyps > 10 mm forceps usage even increased (P < 0.0001). Endoscopists’ forceps removal rates for polyps ≥ 5 mm correlated significantly with respective adenoma detection rates (P = 0.0007, rp – 0.187) and cecal intubation rates (P = 0.0001, rp – 0.303). Among endoscopists in private practices, internists had slightly lower forceps removal rates for polyps ≥ 5 mm than surgeons, both before (47.2 % vs. 50.7 %; P = 0.014) and after publication of the guidelines (51.9 % vs. 53.5 %; P = 0.161).Conclusions: This study confirmed the importance of the European guidelines. The inclusion of adequate resection technique as a quality indicator in colorectal cancer screening programs is recommended.